Negative-Worded Items Functioning as Method Artifacts in the Chemistry Identity Scale: Evidence from Exploratory, Confirmatory, and Bifactor Analyses - Yuleks Juru Mudi; Aeda Kasrianti; Sefthy P B Syahailatua; Nurul Isnaini; Balthasar Eba (Integrated Science Education Journal, 2026)
Purpose of the study: Chemistry identity is an important affective construct in science education because it is associated with learning engagement, academic persistence, and STEM career aspirations. This study aims to evaluate whether negatively worded items represent substantive dimensions of the construct or merely methodological artifacts. Methodology: This study involved 300 senior high school students in Indonesia who completed the Chemistry Identity Scale, consisting of 27 items, including five negatively worded items. Data were analyzed using a comprehensive psychometric approach that incorporated exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and bifactor modeling to distinguish substantive construct variance from method variance attributable to item wording. Main Findings: The findings showed that negatively worded items tended to form a distinct cluster during the exploratory stage, indicating shared method variance. The best-fitting CFA model was the four-factor model with an additional negative wording method factor. Bifactor analysis revealed the dominance of a general chemistry identity factor; however, negatively worded items contributed minimally to the general construct, suggesting that these items function more as sources of method variance than as substantive indicators. Novelty/Originality of this study: The novelty of this study lies in its comprehensive evaluation of wording effects in chemistry identity measurement through the integration of EFA, competitive CFA, and bifactor modeling. These findings have practical implications for educational instrument developers, highlighting the need for greater caution when using negatively worded items, as they may affect score interpretation and lead to less accurate evaluative decisions.